Berani Mencoba, Berani Berhasil: Program Peningkatan Self-Efficacy dan Hope Pada Siswa SMP - Siti Syaffiqah; Jovan Pratama; Ayu Wulandari; Andriyansyah Suhendar; Siti Fakhira Maharani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Failure and fear of failure often cause junior high school students to lose confidence in their abilities, highlighting the need for positive psychology interventions to enhance self-efficacy and hope. This study aimed to examine changes in self-efficacy and hope levels among junior high school students following a positive psychology intervention program. A quantitative method with a pre-experimental one-group pre-test and post-test design was employed, involving eight students aged 12–13 years. The intervention was conducted over two days across four sessions, consisting of psychoeducation, group discussion, interactive games, reflective activities (Tree of Success and Letter to Myself), social modeling through inspirational videos, and a Wall of Support activity. Measurements were taken using the General Self-efficacy Scale (GSES) and the Children’s Hope Scale (CHS). Results showed that the mean self-efficacy score decreased from 34.63 to 32.63, while the mean hope score remained unchanged at 20.63, although individual variations indicated improvement among several participants. Observational data revealed active participant engagement throughout the intervention, suggesting the program's potential benefits despite the lack of significant quantitative change, likely due to the short intervention duration. This study contributes to the development of psychological intervention programs in educational settings, particularly in fostering self-confidence and hope among junior high school students, and serves as a foundation for future research with longer durations and more comprehensive designs.